Duplex Scheme of the Technological Impact of the Provision of Operational Properties of a Hardened Large Module Gears - Hasanov, Magomed; Klochko, Alexander; Horoshaylo, Vadim; Vorontsov, Borys; Ryazantsev, Anton (International Journal of Integrated Engineering, 2022)
The two-level circuit of technological influence of providing of operating properties of hard-tempered large module gears is offered on basis division of tasks of technologist and designer with regulation of complex parameters on each of these stages and subsequent decision of task of choice of optimum value of operating properties.